The RIPASA scoring system: A new Era in appendicitis diagnosis. (August 2022) - Mumtaz, Hassan; Sree, Gummadi Sai; Vakkalagadda, Naga Praneeth; Anne, Krishna Kishore; Jabeen, Sidra; Mehmood, Qasim; Mehdi, Zainab; Sohail, Hassan; Haseeb, Abdullah; Zafar, Yumna; Saghir, Shaima; Hasan, Mohammad
Abstract: Introduction: Even though acute appendicitis is a common acute abdominal disease, it is nonetheless difficult to detect. In order to minimize the risk of complications and negative exploratory procedures, early and accurate diagnosis is critical. We aimed to compare the predictive accuracy of the RIPASA score in diagnosing acute appendicitis with the gold standard of histopathological proven appendicitis as the gold standard. Methodology: A Prospective Cohort Study was conducted from December 2021 to May 2022 at KRL Hospital. A total of 171 patients who sought treatment for acute RIF pain or suspected appendicitis were included in the study. Patients' surgical proclivities were judged in part based on images and surgeon's expertise. SPSS version 26 was used to enter and analyze the data. This was done using a chi-square test and a Kendall's Tau (Kendall Rank Correlation Coefficient) to evaluate both groups of patients. Results: At diagnosis, the mean age was 37.93 10.36 years. Kendall's Tau and Chi Square were shown to be significant in contrast to Alvarado scoring. RIPASA Scoring exhibited a 98.02% positive predictive value, a 96.75% sensitivity, an 82.35% specificity, and 95.3% diagnostic accuracy. Conclusion: The RIPASA score is superior to the Alvarado score when it comes to detecting acute appendicitis in Asian populations. With a brief medical history, a clinical examination, and two simple procedures, parameters can be simply and swiftly obtained in any demographic circumstance. Highlights: Appendicitis decision-making relies on a variety of scoring systems. The RIPASA scoring system has become the new standard. Researchers compared Modified Alvarado and Appendicitis Inflammatory Response score and Raja Isteri Pengiran Anak Saleha Appendicitis score systems. Appendicitis Inflammatory Response score and Raja Isteri Pengiran Anak Saleha Appendicitis score had superior sensitivity, specificity, and diagnostic accuracy than Modified Alvarado. Appendicitis Inflammatory Response score and Raja Isteri Pengiran Anak Saleha Appendicitis scoring system have better accuracy than Modified Alvarado as diagnostic systems.